A importância dos sistemas de informação como suporte a implantação da ISO 9000 - Queirós, José Reinaldo de (2010)
This paper addresses the relationship between information systems and quality management. The information system in conjunction with information technology make up the tool able to implement a flow of information throughout the process and its exchange with suppliers of services or products, and customers, consolidating all information pertinent to the business. The quality management system based on ISO 9000 ensures the manufacturing of products consistently, through a set of procedures that mention, among other points, about the need to standardize processes, provide resources and relevant information to support its operation and monitoring and establish appropriate processes communication both internally and externally to the company; with the primary aim of satisfying customer. Through this survey aimed to identify the importance of information systems as support the ISO 9000 implementation from compatibility of the standard requirements with the functionality of these systems. For both, was conducted a case study in a steel company, whose data was collected through interview with four coordinators, five supervisors, five employees of the shop floor, five suppliers and five customers, in addition to the direct observation. The collected data were analyzed using statistical software and in the light of theoretical contribution considered. The first analysis ensured the convergence of the coordinators responses (technology management and information technology) with the facilitators, the employees of the shop floor, the business partners (suppliers and customers) and what was observed business units (production, information technology and human resources) after submitting the number of convergent responses of each group to software R and use the Fisher's exact test. The second analysis demonstrated the linkage of evidence to reveal the clear links between the questions prepared, collected data and findings from the theory investigated. Thus, we conclude that the information system of this company, it was extremely important to the implementation, and is currently relevant to the maintenance of quality management system based on ISO 9000. Additionally, the information system promoted some benefits to the quality management system, such as: quickest reaction to problems and opportunities, improving information processes, establishment of an information network with all stakeholders, and domain information.